Comparative Analysis of Bacterial Tick-Borne Pathogens in Questing Ticks from Sambia Peninsula, Kaliningrad Oblast, Russia: Spring and Autumn Prevalence and Public Health Risks - Alexey V. Rakov; Evgenii G. Volchev; Ketevan Petremgvdlishvili; Tatiana A. Chekanova (Microorganisms, 2025)
The Kaliningrad Oblast, located in the westernmost part of Russia and bordering European Union countries, is a popular tourist destination. However, limited research has been conducted on the bacteria found in ticks in this region. We, therefore, investigated the prevalence of certain bacteria, including Borrelia, Rickettsia, Anaplasma, and Ehrlichia, as well as the genospecies of the spotted fever group Rickettsia (SFGR) in Ixodes ricinus and Dermacentor reticulatus tick species. To accomplish this, we employed commercial qPCR for pathogen screening. We identified specific genospecies by sequencing the gltA and ompA gene fragments. In I. ricinus ticks, we found Borrelia burgdorferi sensu lato DNA in 35.6% of samples. We also found Rickettsia helvetica in 17.5% of ticks. Additionally, we detected Borrelia miyamotoi in 1.7% and Anaplasma phagocytophilum in 2.6%, while Ehrlichia chaffeensis/Ehrlichia muris were present in 0.6%. In D. reticulatus ticks, we detected only Rickettsia conorii subsp. raoultii DNA, with a prevalence of 6.1%. These findings demonstrate a substantial risk of Lyme disease and other tick-borne infections from early spring through late autumn, emphasizing the importance of ongoing monitoring for these pathogens in the region.